Case Report: Severe Anemia Associated With an Abomasal Fibrosarcoma in a Goat - Wagener, Matthias Gerhard; Beythien, Georg; Sterneberg, Markus; Polifka, Antje; Großmann, Thekla; Baumgärtner, Wolfgang; Ganter, Martin (Frontiers in Veterinary Science, 2022)
A ten-year-old female goat was presented to the clinic with lethargy, emaciation, and pale mucous membranes. Laboratory diagnosis revealed severe anemia with regenerative character as well as melena. Blood transfusions were administered, but the animal’s condition continued to deteriorate, so it was euthanized. The main finding in the necropsy was an abomasal neoplasia with two metastases in the mesenterium which was positive for vimentin, but negative for smooth muscle actin and c-kit using immunohistochemistry, indicating a fibrosarcoma that might have contributed to gastrointestinal blood loss. Further pathological findings consisted of changes in the liver cells as well as a cervical leiomyoma. These findings illustrate that intestinal blood loss due to neoplasia should also be considered in older goats with anemia.